Analisis Volume dan Biaya pada Proyek Pembangunan Rumah Tinggal Berbasis BIM 5D (Studi Kasus Proyek Pembangunan Rumah Tinggal 3 Lantai Tipe 130 di Kota Balikpapan) - Rachman, Tiara Annisa; Hendriyani, Irna; Pratiwi, Reno (Universitas Batanghari Jambi, 2024)
The development of information and communication technology in the construction industry has significantly advanced in recent years. One of the latest innovations is Building Information Modeling (BIM). This research compares the volume and cost of structural work between the BIM 5D concept and the consultant's results for a 3-storey residential building in Karang Rejo, Central Balikpapan. Using Autodesk Revit, 2D drawings from the consultant were transformed into 3D models. The consultant calculated the concrete volume at 45.26 m³, whereas Autodesk Revit showed 39.34 m³, a difference of 5.92 m³ or 13.08%. For reinforcement work, the consultant's volume was 7,047.95 kg, while Autodesk Revit calculated it at 6,076.28 kg, showing a difference of 971.67 kg or 13.79%. The cost of concrete work was Rp 67,954,242.07 according to the consultant, while Autodesk Revit showed Rp 59,096,016.16, a difference of Rp 8,858,225.91 or 13.04%. The cost of reinforcement work was Rp 125,881,320.57 according to the consultant, while Autodesk Revit calculated it at Rp 108,521,878.90, with a difference of Rp 17,359,441.67 or 13.79%. Using the BIM 3D concept with Autodesk Revit provides more detailed material takeoff results, reduces material waste, and supports the BIM 5D concept for more accurate cost estimation.